2015
DOI: 10.1186/s12863-015-0255-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ethnicity on the distribution of genetic polymorphisms associated with risk of chronic liver disease in South American populations

Abstract: BackgroundThe global burden of chronic liver disease is rising. Besides environmental, behavioral, viral and metabolic factors, genetic polymorphisms in patatin-like phospholipase-3 (PNPLA3) and vitamin D receptor (VDR) genes have been related to the development of chronic liver disease and progression towards liver cancer. Although their prevalence differs remarkably among ethnic groups, the frequency of these polymorphisms in South American populations -whose genetic background is highly admixed- has been po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 47 publications
3
24
0
1
Order By: Relevance
“…24 Santos et al (2009) described the participation of Europeans (60%), native Indians (28%), and Africans (12%) in the foundation of the city of Belé m. 31 Recent studies have demonstrated that the genetic influence of ethnicity or ancestry might be related to variations in the genes involved in the individual's responses to certain diseases. 25,32 Therefore, the level of ethnic diversity present in the study population may influence the frequency of the CYP2B6 G516T polymorphism compared with different ethnic groups. The frequency of the polymorphic allele previously determined for individuals in the city of Belé m who were receiving treatment for tuberculosis (0.30) is similar to the frequency found in the present study (0.36).…”
Section: Discussionmentioning
confidence: 99%
“…24 Santos et al (2009) described the participation of Europeans (60%), native Indians (28%), and Africans (12%) in the foundation of the city of Belé m. 31 Recent studies have demonstrated that the genetic influence of ethnicity or ancestry might be related to variations in the genes involved in the individual's responses to certain diseases. 25,32 Therefore, the level of ethnic diversity present in the study population may influence the frequency of the CYP2B6 G516T polymorphism compared with different ethnic groups. The frequency of the polymorphic allele previously determined for individuals in the city of Belé m who were receiving treatment for tuberculosis (0.30) is similar to the frequency found in the present study (0.36).…”
Section: Discussionmentioning
confidence: 99%
“…Some data from Latin America show a high prevalence of p.I148M in the general population and even higher prevalence in individuals with Native American ancestry. A preliminary study from Chile reported an allelic frequency of the high‐risk allele G of 59% in the general population, whereas in Argentina, Pontoriero et al reported in a study involving 258 healthy unrelated male volunteers that the GG genotype of PNPLA3 rs738409 was present in 63.7% of individuals with maternal and paternal Native American ancestry. It is important to consider that admixture of Native Americans, Europeans, and Africans is variable throughout Latin America, which makes the genetic makeup of each country considerably heterogeneous .…”
Section: Factors Responsible For the Higher Prevalence Of Nafld In Lamentioning
confidence: 99%
“…15 The PNPLA3 polymorphism seems to be more prevalent in persons of native-American ancestry from South America compared with non-native South Americans; for example, those of Spanish, European, and African ancestry. 16 A high frequency of PNPLA3 variants and a strong association of these variants with increased serum alanine aminotransferase (ALT) levels has been found in indigenous Mexican and Mestizo peoples. 17 In white Europeans, the PNPLA3 polymorphism is more common in patients with ALD compared with controls and is significantly associated with the presence of steatosis, fibrosis, and cirrhosis.…”
Section: Epidemiology Of Alcoholic Liver Diseasementioning
confidence: 99%